Design of Time Synchronization Method for Real-Time EPON - Junsuo QU (Institute of Advanced Engineering and Science, 2013)
Real-time performance problems are mainly obstacles on Ethernet used in industrial control. In this paper, a RT-EPON concept can be proposed, and the frame structure, the protocol of RT-EPON MAC, and time slot allocation mechanism have been designed. In a test system, the designed Mac protocol and time synchronization method have been tested, it is shown that the RT-EPON system is stable and reliable, and the BER (Bit Error Rate) is below 10-10 on the physical layer of fiber link.DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2079